Gamification in Islamic Religious Education: Developing Interactive Learning Media via Quizizz with the Addie Model - Sakdiah; Hayati; Salami Mahmud; Muhammad Furqan (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
This study aims to develop gamified learning media using the Quizizz application for the Islamic Religious Education and Character subject. The research was conducted at public junior high schools in Banda Aceh, Indonesia, involving Grade VII students and Islamic Education teachers who had experience implementing digital media in the classroom. The study was driven by the low levels of student motivation and participation caused by the dominance of conventional lecture-based methods. Quizizz was chosen as the development platform for its game-based features—such as points, leaderboards, avatars, and instant feedback—that are known to enhance student engagement and interaction. A Research and Development (R&D) approach was employed using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), providing a systematic framework for the creation, testing, and refinement of the gamified media. Data were collected through participatory observation, semi-structured interviews, and documentation, and analyzed qualitatively using an interactive model. Each phase of ADDIE was integrated with data collection: identifying student learning needs, designing gamified content based on Islamic values, developing the product with expert validation, implementing it through field trials, and evaluating its impact. The findings demonstrate that the gamified media effectively fostered a more interactive, enjoyable, and motivational learning atmosphere. There was a significant increase in students’ engagement, participation, and academic achievement. Teachers also reported positive experiences using Quizizz for instruction and real-time assessment. The study concludes that gamification can serve as an effective pedagogical innovation for Islamic education, promoting meaningful learning experiences aligned with religious and character-building goals.